2019
DOI: 10.1055/s-0039-1696714
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Volumes and Outcome of Extubation in Mechanically Ventilated Premature Infants

Abstract: Objectives To compare the adjusted and unadjusted-for-weight tidal volume (VT) in ventilated prematurely born infants who were successfully extubated compared with the ones who failed extubation and explore the ability of VT to predict successful extubation. Study Design This is a two-center, prospective, observational, cohort study of ventilated infants born <32 weeks of gestational age (GA) at King's College Hospital and St George's University Hospital, London, United Kingdom between February an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Others have shown demographic data such as the gestational age and body weight were better predictors of successful extubation than assessment of physiological variables [9,10,[13][14][15]. In a recent study, however, we demonstrated that a higher tidal volume in prematurely born infants better predicted extubation success than gestational age after adjustment for confounders [16]. In the study currently reported, we also found that the tidal volume and neuroventilatory efficiency differed significantly between those who were and were not successfully extubated.…”
Section: Discussionmentioning
confidence: 54%
“…Others have shown demographic data such as the gestational age and body weight were better predictors of successful extubation than assessment of physiological variables [9,10,[13][14][15]. In a recent study, however, we demonstrated that a higher tidal volume in prematurely born infants better predicted extubation success than gestational age after adjustment for confounders [16]. In the study currently reported, we also found that the tidal volume and neuroventilatory efficiency differed significantly between those who were and were not successfully extubated.…”
Section: Discussionmentioning
confidence: 54%
“…It is interesting to note that the debate on whether efficient ventilation can occur with tidal volumes that are lower than the dead space refers predominantly to the extremely preterm infants as the contribution of the fixed amount of the instrumental dead space is relatively higher in the smallest infants, which are the ones that would benefit more from lung-protective ventilation strategies. A very low targeted tidal volume though, is not always lung protective, as too small volumes have been associated with an increased work of breathing ( 35 ), a higher incidence of extubation failure ( 36 ) and a pro-inflammatory state ( 8 ). A potential practical recommendation that emerges from our results is that the targeted tidal volume in ventilated preterm infants should not be lower than the total anatomical, alveolar and instrumental dead space and very low targeted tidal volumes (below 5 ml/kg) should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Dassios et al5 conducted an adequately powered cohort study, which found pulling tidal volumes more than 4.5 mL/kg as statistically significant for predicting successful extubation of ventilated infants less than 32 weeks of gestational age. Dassios et al5 also utilized guidelines for considering extubation as well as specific reintubation criteria for consideration.…”
Section: Literature Reviewmentioning
confidence: 99%